2008
DOI: 10.3747/co.2008.176
|View full text |Cite
|
Sign up to set email alerts
|

After Radiotherapy, Do Bone Metastases from Gastrointestinal Cancers Show Response Rates Similar to Those of Bone Metastases from Other Primary Cancers?

Abstract: Bone is the most common site for distant spread of breast cancer. Following a diagnosis of metastatic bone disease, patients can suffer from significant morbidity because of pain and skeletal related events (sres). Bisphosphonates are potent inhibitors of osteoclastic function and the mainstay of bone-directed therapy for bone metastases. The aims of bisphosphonates are to prevent and delay sres, to reduce bone pain, and to improve quality of life. Bisphosphonate therapy appears to have revolutionized treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 73 publications
0
18
0
1
Order By: Relevance
“…Depending on the nature of the imminent or actual skeletal complication, a wide variety of treatment options are available to treat bone metastases, including systemic treatment with bisphosphonates, radiation therapy, ablation, vertebroplasty, and surgery (15). Bisphosphonates are potent inhibitors of osteoclast-mediated bone resorption and reduce skeletal complications and provide some pain relief (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the nature of the imminent or actual skeletal complication, a wide variety of treatment options are available to treat bone metastases, including systemic treatment with bisphosphonates, radiation therapy, ablation, vertebroplasty, and surgery (15). Bisphosphonates are potent inhibitors of osteoclast-mediated bone resorption and reduce skeletal complications and provide some pain relief (15).…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates are potent inhibitors of osteoclast-mediated bone resorption and reduce skeletal complications and provide some pain relief (15).…”
Section: Discussionmentioning
confidence: 99%
“…49,50 The orally administered bisphosphonates clodronate and ibandronate have shown some effi cacy in preventing SREs in patients with breast cancer. 51 For these agents, the apparent convenience of oral administration is undermined by the need to follow a strict dosing regimen that requires fasting before ingesting the drug and remaining upright for a specifi ed duration afterward. Compliance with dosing regimens for oral bisphosphonates is poor overall, 52 and these regimens may be especially challenging for patients with thoracic tumors that may constrict the esophagus.…”
Section: Patient Adherence To Therapeutic Regimensmentioning
confidence: 99%
“…24,118,119 The humanized monoclonal antibody to the IL-6 receptor, tocilizumab (Actemra ® ) was approved by the United States Food and Drug Administration (FDA) on January 11, 2010 and was previously approved in Japan and the European Medicines Agency (EMEA) in 2008 (Table 1). 120 Although tocilizumab is approved only for rheumatoid arthritis (RA) in the United States and Europe as well as Castleman's disease in Japan, recent studies have shown that tocilizumab is also effective as an antitumor agent against U87MG glioma cells.…”
Section: Il-6 As a Target For Therapymentioning
confidence: 99%